The Use of Group-Work, Reward-Punishment, and Visual Media as an Integrated Teaching-Learning Strategy to Improve the EL T Classroom Interaction of the 8th Grade Students of MTs NW Hikmaturrahim, Lombok Tengah - Yek Amin Azis; Asruddin Barori Tou (JOURNAL OF EDUCATION, 2013)
This research aimed at observing and describing the processes and the results of the actions implemented in improving the ELT classroom interaction of the gh grade students of MTs NW Hikmaturrahim,  Lombok Tengah. This research was a collaborative action research study. The subjects were the English teacher and the gh grade students of MTs NW Hikmaturrahim, Lombok Tengah in the academic year of 201112012. There were two steps in conducting this research, namely reconnaissance and action. The research instruments used in this study were  observation sheets  and  questionnaire. The data  were  collected through observation and questionnaire. The results of the research are as follows. After implementing the  group-work,  reward-punishment, and  visual  media  as  an integrated teaching-learningstrategy in two cycles, the students were not afraid in speaking, all groups felt  brave to speak with the English teacher or with other students, almost all of the students were active in the classroom interaction with the English teacher or with other students, the students were more motivated to study than before, it could overcome the students' laziness to study, and, the students were interestedin the ELT process.